Kemampuan Membaca Memahami Teks Dialog Bahasa Jerman - Umar, Nurul Annisa Auliah; Al-Ilmullah, Syarifah Fatimah; Mannahali, Misnah (Universitas Negeri Makassar, 2024)
Abstract. Falling This study aims to determine the level of reading comprehension ability of German dialog text of students in class XI MIPA SMA Negeri 4 Maros. The research used quantitative descriptive method. Written texts were used for data collection. The text consists of multiple choice and true and false tests. Furthermore, the data were analyzed using percentage technique. The population in this study was XI MIPA class students at SMA Negeri 4 Maros consisting of 5 classes with 160 students. The samples of this study were students of class XI MIPA 3 as many as 31 students who were selected using random sampling. The result of this study showed that the ability to read comprehend German dialog text of students of class XI MIPA 3 SMA Negeri 4 Maros was in the good category.Keywords: Skill, Reading Comprehension, Dialog Text